POSISI STRATEGIS KAB. KEPULAUAN TALAUD SEBAGAI LALULINTAS PERDAGANGAN INTERNASIONAL DALAM RANGKA MEA (Suatu Kajian Historis Kultural) - Pratiknjo, Maria Heny (HOLISTIK, Journal Of Social and Culture, 2018)
Talaud Islands Regency located right on the lip of the Pacific since the days BC experiencing a heyday where when it though barter trade system are still but community prosperous life. The Islands in the term length was Maleon (Karakelang), Sinduane (Salibabu), Tamarongge (Kabaruan), Batunampato (Nanusa) and Tinonda is Miangas. Barter Trade and the system of monopoly in spice trade by European countries have established trade colonies aiming to monopolize the spice trade in the region including the Islands clusters.Â Keywords: Talaud Islands, trade, barter